DAMPAK KEBERADAAN USAHA TAMBAK UDANG DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA TAMBAK SARI KECAMATAN POTO TANO KABUPATEN SUMBAWA BARAT (STUDI KASUS PT. BUMI HARAPAN JAYA) - Yuliana, Yuliana; Sahar, Sahar (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2022)
This study is entitled "The Impact of Shrimp Pond Business in Increasing Community Welfare in Tambak Sari Village, Poto Tano District, West Sumbawa Barat (Case Study of PT. Bumi Harapan Jaya). This type of research is a qualitative research with a descriptive approach and uses Observation, Interview and Documentation activities as data collection techniques. Informants from this study consisted of the Tambak sari Village Community, company staff, employees and Tambak sari Village officials, Poto Tano District, West Sumbawa Barat, The technique used in testing data validity uses triangulation techniques that combine Results and Data from field findings. The results show that the impact of the existence of shrimp ponds can improve the welfare of people's lives and provide employment opportunities for the community of ponds and provide a definite additional income each month.